JHEA, Volume 8, n° 1, 2010 - Full Issue - Journal System (Journal of Higher Education in Africa, 2010)
Contents Teaching and Researching Africa in an ‘Engaged’ Way: The Possibilities and Limitations of ‘Community Engagement’ Sally Matthews ................................... 1 L’enseignement supérieur au Maroc : de l’autonomie à la dépendance ? Ahmed Ghouati .................................. 23 Academic Freedom and Dual Career Academic Couples: The Complexities of Being a Woman Academic in the University Space Chinyere Ukpokolo ............................... 49 In Search of Sources other than Governmental in the Financing of Higher Education in Sub-Saharan Africa: A Word of Caution Beyond the Gains Touorouzou Herve Some ............................. 73 GATS and Higher Education in Nigeria: A Preliminary Investigation of the Indicative Patterns of Consumption Abroad by Nigerians Olanrewaju Olaniyan, Abiodun S. Bankole & Olugboyega A. Oyeranti.. 99 The Relationship between Vice-Chancellors’ Leadership Behaviour and the Work Behaviour of Lecturers in Nigerian Universities: Implication for Leadership Training for Vice-Chancellors Ganiyu G. Oke, P.O. Okumola, Adesoji A. Oni & J.A. Adetoro ........ 123